Self‐Assembling Amphiphilic Hyperbranched Polyglycerol–Polystyrene Copolymers for Encapsulation. Issue 16 (14th July 2015) - Ernenwein, Dawn; Vartanian, Ariane M.; Zimmerman, Steven C.
<x xml:space="preserve">Abstract</x> Phospholipids, dendrimers, and polymers are each able to assemble to form vesicles, but each has limitations such as leakiness and multistep syntheses. A new class of versatile amphiphilic block copolymers is reported containing hyperbranched polyglycerol (HPG) and polystyrene (PS) units. These compounds self‐assemble into polymersomes (HPGsomes). Under solvent exchange methods, amphiphilic polystyrene‐HPG diblock (PS‐b‐HPG) structures are self‐assembled and characterized by transmission electron microscopy. The assemblies are robust up to 95 °C in polar, protic solvents, and encapsulate dyes with minimal release. Polymersomes are typically assembled from linear amphiphilic polymers; however, it is shown that combining linear and hyperbranched polymers is a feasible strategy to encapsulation.